2007
DOI: 10.3732/ajb.94.4.690
|View full text |Cite
|
Sign up to set email alerts
|

Chaetomium elatum (Kunze: Chaetomiaceae) as a root‐colonizing fungus in avocado: is it a mutualist, cheater, commensalistic associate, or pathogen?

Abstract: Plants support numerous root colonists that may share morphological characteristics with mycorrhizal fungi but may play different roles in the rhizosphere. To determine the function of one such root-colonizing fungus, Chaetomium elatum, the infectivity and composition of inoculum containing C. elatum were varied independently of and in association with the known mutualist Glomus intraradices under two light intensities. Maximum plant benefit occurred with mixtures of both G. intraradices and C. elatum and unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 58 publications
1
20
1
Order By: Relevance
“…Of these FCspecific OTUs, many were assigned to phylogenetic groups harboring known phytotoxic or phytopathogenic microorganisms, such as the fungal genera Periconia, Curvularia, and Aspergillus, the fungal order Pleosporales, the fungal family Chaetomiaceae, and the bacterial class Gammaproteobacteria (58)(59)(60)(61)(62)(63). While these results do not directly implicate microorganisms in the creation and/or maintenance of Namib Desert FCs, they remain consistent with the hypothesis that microorganisms play a role in the phenomenon.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Of these FCspecific OTUs, many were assigned to phylogenetic groups harboring known phytotoxic or phytopathogenic microorganisms, such as the fungal genera Periconia, Curvularia, and Aspergillus, the fungal order Pleosporales, the fungal family Chaetomiaceae, and the bacterial class Gammaproteobacteria (58)(59)(60)(61)(62)(63). While these results do not directly implicate microorganisms in the creation and/or maintenance of Namib Desert FCs, they remain consistent with the hypothesis that microorganisms play a role in the phenomenon.…”
Section: Discussionsupporting
confidence: 70%
“…Finally, we have identified microorganisms that are present solely in FC soils and that may play a role in the fairy circle phenomenon. Many of the OTUs found only in FCs are related to known phytopathogen groups (the fungal genera Periconia, Curvularia, and Aspergillus, the fungal order Pleosporales and family Chaetomiaceae, and the bacterial class Gammaproteobacteria [58][59][60][61][62][63]), suggesting that they may play a role in this phenomenon. To further investigate this hypothesis, the FC-specific phylotypes should be isolated and used in controlled greenhouse experiments to identify patterns related to phytopathology (64).…”
Section: Discussionmentioning
confidence: 99%
“…Re-synthesis in vitro co-culture system will be required, however, to confirm their endophytism and infection structure in roots. In addition, increasing reports have demonstrated that some novel groups of DSEs are classified into the order Pleosporales (Jumpponen 2001;Violi et al 2007;Porras-Alfaro et al 2008). In our study, molecular phylogeny revealed that four genotypes (Genotype 13-16) fell into the order Pleosporales (data not shown), which may act as potential DSEs but also waiting to be verified by using in vitro experimentation.…”
Section: Resultscontrasting
confidence: 50%
“…Root-colonizing fungi may have various lifestyles, depending on the plant's physiology and the availability of resources (Redman et al 2001;Violi et al 2007); this certainly may be the case for endophytic fungi.…”
Section: Discussionmentioning
confidence: 99%